Dynamic Behavior and Force Analysis of the Full Vehicle Model using Newmark Average Acceleration Method - Yildirim, E.; Esen, I. (Engineering, Technology & Applied Science Research, 2020)
In this study, the dynamic interaction between road and vehicle is modeled. For this purpose, a full vehicle model with eight degrees of freedom is considered. The equations of motion of the whole system are derived by the D’Alambert method and numerical solutions are obtained by the Newmark average acceleration method. Due to varying road roughness, the forces affecting the driver and the vehicle-components are analyzed in detail. Also, vertical and rotational displacements, velocities, and accelerations are examined, and results graphs are given. Two different pre-defined road profiles, created as non-random road excitation, and five different vehicle speeds are presented and analyzed.